Suspected Intestinal Tuberculosis Might Be Crohn's Disease - Semiu Eniola Folaranmi; Gautam Mehta; Debasis Datta; Greg Holdstock (Case Reports in Medicine)
In this case report we provide evidence that supports a link between mycobacteria and Crohn's disease. The patient in question, KG, presented on three separate occasions over a ten years period with features suggestive of intestinal tuberculosis. He was treated successfully on each occasion with antimycobacterial drugs. When he presented a fourth time with the same symptoms, he was diagnosed with Crohn's disease based on findings from endoscopy, histology and CT. Subsequently he was treated with a course of steroids and made a full recovery. This case adds weight to the theory that mycobateria has an aetiological role in Crohn's disease.